Handbook on Gender and Public Administration, By Patricia M. Shields and Nicole M. Elias. Northampton: Edward Elgar Publishing, 2022 - Suparna Soni (Journal of Social Equity and Public Administration)
The Handbook on Gender and Public Administration, edited by Patricia M. Shields and Nicole M. Elias, is a crucial foundational text for integrating a gender-focused perspective into public administration scholarship and practice. This comprehensive work examines the intersection of gender with policy and practice, tracing the discipline's historical trajectory, current status, and future directions. Roddrick Colvin, in the foreword, rightly underscores the urgent need for this work, emphasizing that men have taken too long to acknowledge and embrace their responsibility in advancing gender equity in public administration.